Research Progress and Prospect Slope Greening in China - Zhang Mengyan; Guo Xiaoping; Zhao Tingning; Ji Xiaodong; Wei Tianxing; Shi Changqing (Shuitu baochi tongbao)
[Objective] The current status and hot trends of slope greening research were studied in order to provide theoretical support and references for subsequent research. [Methods] Professional bibliometric tools CiteSpace and VOSviewer were used to visualize and analyze slope greening research literature indexed by the China National Knowledge Infrastructure (CNKI) database. The main indicators included publication volume, high-frequency keywords, keyword co-occurrence clusters, and burst keywords. The research hotspots and changes in research trends were discussed from three aspects: mechanisms of slope root fixation of soil, selection and configuration of slope plants, and application of engineering greening technology. [Results] There has been a good trend of publishing scientific research results in the field of slope greening in China. Research institutions were mostly higher education institutions (colleges and universities) with programs in the fields of agriculture, forestry, science, and engineering. As a multidisciplinary and comprehensive application technology, slope greening has a very necessary role to play in industry associations. [Conclusion] At present, the variation pattern of slope stability is an important research direction. Numerical simulation technology is expected to play a greater role in the study of slope stability. Plant screening research has focused on the ecological adaptability of plants, which can strengthen future investigations and breeding efforts related to plants adapted to slope protection in the region. Determining the factors influencing plant diversity changes can contribute to the sustainability of plant configuration. Spraying was found to be the most widely used greening technology. The topics of erosion resistance and stability of substrate materials were research hotspots. In the future, it will be necessary to start with the standardization of terminology, construction methods, equipment, and materials so as to gradually establish a standard system for spraying and greening technology applicable to conditions found in China.